Rejoinder to Professor Ho's team on the article entitled 'On evolutionary economic geography: a literature review using bibliometric analysis'. Issue 6 (3rd June 2019) - Zhu, Shengjun; Jin, Wenwan; He, Canfei
ABSTRACT: Professor Ho's team has raised three questions about our paper entitled 'On evolutionary economic geography: a literature review using bibliometric analysis' published in European Panning Studies. The first one is about the number of articles in our search results. The second one is about the databases we have used in the Web of Science system. In the last comment, Professor Ho suggests a new searching strategy – 'front page' rule. We have responded to those three comments one by one in this rejoinder.